Desafios da cooperação Sul-Sul: o processo de desindustrialização precoce do Brasil, a China como catalisador? - Portela, Polianna de Almeida (2021)
The present dissertation proposes to analyse the early deindustrialization of Brazil in the scope of the Sino-Brazilian relationship (2000-2018), which has South-South Cooperation as its driving scenario. This research presents three distinct essays, which complement each other in order to understand whether China acts as a catalyst in the process of early deindustrialization of Brazil. Therefore, the first scenario presents South-South Cooperation to understand how China uses the discourse of equal gains, mutual development and symmetric partnerships, to foster its alliance with Brazil, based on the assumptions of the New Structural Economy (New Structural Economics). The second scenario presented is the endogenous Brazilian structure, since it recognizes the existence of structural problems of economic, political and social basis that, by themselves, drive the process of early deindustrialization. Thus, the country's position as the periphery of the capitalist system, as well as issues ranging from the absence of capital to sustain the national productive transformation to the predominance of inequality, the strong presence of large land properties, the maintenance of structural heterogeneity, the structural inflation, weak institutions, the absence of a Schumpeterian elite are taken into account. In this second context, it is shown how the endogenous structure plays a relevant role in the results presented by the Brazilian economy. The third and last scenario conducts an inquiry into the deindustrialization process within the framework of the Sino-Brazilian bilateral relationship. At first, the main concepts on early deindustrialization are delimited, understanding that there is a divergence on how it is delimited. Finally, economic complexity is discussed to complement the structuralist discussion on the central role of the productive structure for a country's economy. Data from the Atlas of Economic Complexity and Chinese investments and loans in Brazil were used in the analysis in order to infer about the premature change in the Brazilian productive structure within the relationship with China.